Using Online Dictionaries 2014
DOI: 10.1515/9783110341287.281
|View full text |Cite
|
Sign up to set email alerts
|

Benutzerwünsche und -meinungen zu dem monolingualen deutschen Onlinewörterbuch elexiko

Abstract: Abstract:In this paper, we present the concept and the results of two studies addressing (potential) users of monolingual German online dictionaries, such as www.elexiko.de. Drawing on the example of elexiko, the aim of those studies was to collect empirical data on possible extensions of the content of monolingual online dictionaries, e.g. the search function, to evaluate how users comprehend the terminology of the user interface, to find out which types of information are expected to be included in each spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Einerseits galt es, durch gezielte Fragen 2 Die Wörterbuchbenutzungsforschung hat sich im Laufe der letzten 20 Jahre zu einem wichtigen Forschungszweig der Wörterbuchforschung entwickelt (vgl. u. a. Bergenholtz/Johnsen 2013; Klosa/ Koplenig/Töpel 2014;Müller-Spitzer Hrsg. 2014;Müller-Spitzer 2016;Tarp 2009;Simonsen 2011;Tiberius/Müller-Spitzer Hrsg.…”
Section: Projektbezogene Wörterbuchbenutzungsstudienunclassified
“…Einerseits galt es, durch gezielte Fragen 2 Die Wörterbuchbenutzungsforschung hat sich im Laufe der letzten 20 Jahre zu einem wichtigen Forschungszweig der Wörterbuchforschung entwickelt (vgl. u. a. Bergenholtz/Johnsen 2013; Klosa/ Koplenig/Töpel 2014;Müller-Spitzer Hrsg. 2014;Müller-Spitzer 2016;Tarp 2009;Simonsen 2011;Tiberius/Müller-Spitzer Hrsg.…”
Section: Projektbezogene Wörterbuchbenutzungsstudienunclassified
“…After all, it is not easy for lexicographers to understand how to make proper use of them in specific e-dictionaries for specific users since related empirical research has provided an unclear picture. Kaneta (2011) found dictionary interfaces influenced both the amount and the length of reference to illustrative examples, and users' choice of interfaces "depends on the quality of information available outside the folded elements" (Lew 2015), but Klosa et al (2014) showed most users chose the expanded view as a default. Dziemianko (2015) proved that color influenced the speed and effectiveness of dictionary search as well as the retention of the retrieved information.…”
Section: Potential Problems With Current E-dictionariesmentioning
confidence: 99%
“…But in huge projects a questionnaire is organized online, as it was done with the German online dictionary elexiko (cf. Klosa, Koplenig and Töpel 2014). The whole process of planning, realization, evaluation, and critical reflection is described in Koplenig and Müller-Spitzer 2014a: 79ff., Müller-Spitzer 2014c: 85ff., Koplenig and Müller-Spitzer 2014b: 127ff., Müller-Spitzer and Koplenig 2014: 143ff., Koplenig and Müller-Spitzer 2014c: 189ff.…”
Section: Research On Dictionary Usementioning
confidence: 99%